Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure, let's solve the given expressions step by step.
### Step-by-Step Solution
#### Expression 1:
[tex]\[ (c + d)^2 \][/tex]
To solve this expression, we need to follow these steps:
1. Identify the variables: Here, [tex]\( c \)[/tex] and [tex]\( d \)[/tex] are the variables in the expression.
2. Sum the variables: Add [tex]\( c \)[/tex] and [tex]\( d \)[/tex].
3. Square the result: Raise the sum to the power of 2.
Given [tex]\( c = 1 \)[/tex] and [tex]\( d = 1 \)[/tex]:
1. [tex]\( c + d = 1 + 1 = 2 \)[/tex]
2. [tex]\((c + d)^2 = 2^2 = 4\)[/tex]
So, the result of the first expression is:
[tex]\[ (c + d)^2 = 4 \][/tex]
#### Expression 2:
[tex]\[ \frac{c}{d} - \frac{m}{n} + 2 \][/tex]
To solve this expression, we need to follow these steps:
1. Identify the variables: Here, [tex]\( c \)[/tex], [tex]\( d \)[/tex], [tex]\( m \)[/tex], and [tex]\( n \)[/tex] are the variables. We need their values.
2. Compute each fraction: Calculate [tex]\( \frac{c}{d} \)[/tex] and [tex]\( \frac{m}{n} \)[/tex].
3. Subtract the fractions and add 2: Subtract the second fraction from the first and then add 2 to the result.
Given [tex]\( c = 1 \)[/tex], [tex]\( d = 1 \)[/tex], [tex]\( m = 1 \)[/tex], and [tex]\( n = 1 \)[/tex]:
1. [tex]\( \frac{c}{d} = \frac{1}{1} = 1 \)[/tex]
2. [tex]\( \frac{m}{n} = \frac{1}{1} = 1 \)[/tex]
3. [tex]\( 1 - 1 + 2 = 0 + 2 = 2 \)[/tex]
So, the result of the second expression is:
[tex]\[ \frac{c}{d} - \frac{m}{n} + 2 = 2 \][/tex]
### Final Results
From solving both expressions, we have:
1. [tex]\((c + d)^2 = 4\)[/tex]
2. [tex]\(\frac{c}{d} - \frac{m}{n} + 2 = 2\)[/tex]
Thus, the results are:
[tex]\[ (4, 2.0) \][/tex]
### Step-by-Step Solution
#### Expression 1:
[tex]\[ (c + d)^2 \][/tex]
To solve this expression, we need to follow these steps:
1. Identify the variables: Here, [tex]\( c \)[/tex] and [tex]\( d \)[/tex] are the variables in the expression.
2. Sum the variables: Add [tex]\( c \)[/tex] and [tex]\( d \)[/tex].
3. Square the result: Raise the sum to the power of 2.
Given [tex]\( c = 1 \)[/tex] and [tex]\( d = 1 \)[/tex]:
1. [tex]\( c + d = 1 + 1 = 2 \)[/tex]
2. [tex]\((c + d)^2 = 2^2 = 4\)[/tex]
So, the result of the first expression is:
[tex]\[ (c + d)^2 = 4 \][/tex]
#### Expression 2:
[tex]\[ \frac{c}{d} - \frac{m}{n} + 2 \][/tex]
To solve this expression, we need to follow these steps:
1. Identify the variables: Here, [tex]\( c \)[/tex], [tex]\( d \)[/tex], [tex]\( m \)[/tex], and [tex]\( n \)[/tex] are the variables. We need their values.
2. Compute each fraction: Calculate [tex]\( \frac{c}{d} \)[/tex] and [tex]\( \frac{m}{n} \)[/tex].
3. Subtract the fractions and add 2: Subtract the second fraction from the first and then add 2 to the result.
Given [tex]\( c = 1 \)[/tex], [tex]\( d = 1 \)[/tex], [tex]\( m = 1 \)[/tex], and [tex]\( n = 1 \)[/tex]:
1. [tex]\( \frac{c}{d} = \frac{1}{1} = 1 \)[/tex]
2. [tex]\( \frac{m}{n} = \frac{1}{1} = 1 \)[/tex]
3. [tex]\( 1 - 1 + 2 = 0 + 2 = 2 \)[/tex]
So, the result of the second expression is:
[tex]\[ \frac{c}{d} - \frac{m}{n} + 2 = 2 \][/tex]
### Final Results
From solving both expressions, we have:
1. [tex]\((c + d)^2 = 4\)[/tex]
2. [tex]\(\frac{c}{d} - \frac{m}{n} + 2 = 2\)[/tex]
Thus, the results are:
[tex]\[ (4, 2.0) \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.